Co-curricular Activities and Students' Confidence Building: A Co-Relational Study at Elementary Level (Contemporary Journal of Social Science Review, 2024)
This research was conducted to determine the association between co-curricular activities and students' confidence building at elementary level. The objectives of the research were (1) To investigate the practices of co-curricular activities at elementary level as perceived by students (2) To analyze students’ confidence building at elementary level as perceived by students (3) To assess the relationship between co-curricular activities and students’ confidence building at elementary education level (4) To discover the variance between the students' opinion about co-curricular activities and students’ confidence building at elementary education level on the basis of demographics variables. To attain the objectives of the research, descriptive quantitative survey design was used. A sample of 857 students consisting 468 males and 389 females studying in 8th class by using the stratified random sampling technique was select. A 74-item questionnaire (for students), self-structured used to determine the association between the co-curricular activities and pupils' confidence building at elementary level. The SPSS was used to analyze the data. The inferential and descriptive statistical techniques were used for the interpretation of the data.  The findings of the research indicated that co-curricular activities showed positive role in building confidence among students.